Sistematic Literature Review: Analisis Pentingnya Kepemimpinan Pada Keselamatan Operasi Penerbangan - Waluyo Setyo Pramono; Surtiningtyas, Sri Rahayu (Jurnal Bisnis dan Operasi Penerbangan, 2024)
This study explores the impact of leadership on aviation operation safety through a Systematic Literature Review (SLR) method. In the aviation industry, safety is a top priority that requires contributions from all employees and effective leadership. Safety leadership is defined as the ability of leaders to promote a safety culture through consistent actions, communication, and policies. This research aims to determine whether leadership has a significant impact on aviation operation safety and to identify influential leadership factors. SLR was chosen for its ability to provide a comprehensive and evidence-based evaluation of existing literature, thereby reducing researcher bias. The search process was conducted using Google Scholar, Research Gate, and Science Direct, with the keywords "Leadership in aviation" and "Leadership in aviation for safety" for the period 2018-2024. Out of 13 journals found, from the 13 journals identified, 10 met the inclusion criteria, and 7 were selected following a quality assessment. The findings indicate that leadership significantly affects aviation operation safety, with key leadership factors including member empowerment, trust in leaders, critical communication, making data-driven decisions, and promoting leadership and safety culture. Focusing on these factors, leadership can enhance aviation operation safety by increasing awareness and implementing effective safety practices.